MODEL COOPERATIVE INTEGRATED READING AND COMPOSITION (CIRC) DALAM MENINGKATKAN PEMAHAMAN MEMBACA PUISI - Asmara, Jonior; Ira Yuniati; Adi Asmara; Reni Kusmiarti; Tomi Hidayat (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to determine the improvement in poetry reading comprehension skills of sixth-grade students of MI Negeri 7 Seluma after the implementation of the Cooperative Integrated Reading and Composition (CIRC) model. This study used a quantitative approach with an experimental research type and a one-group pretest-posttest design. The research subjects were 9 sixth-grade students in the even semester of the 2025/2026 academic year. The data collection technique used a poetry reading comprehension test given before (pretest) and after (posttest) the treatment. The data were analyzed through normality tests and hypothesis tests using the Paired Sample t-Test with the help of SPSS version 27. The results showed that the average pretest score was 58.7778 with a standard deviation of 6.28048, while the average posttest score increased to 83.6667 with a standard deviation of 6.08276. The results of the Paired Sample t-Test showed a significance value (2-tailed) of 0.000 <0.05, so H₀ was rejected and Hₐ was accepted. Thus, it can be concluded that the application of the Cooperative Integrated Reading and Composition (CIRC) model significantly improved the poetry reading comprehension ability of sixth-grade students of MI Negeri 7 Seluma.